2005
DOI: 10.1111/j.1399-3062.2005.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized control trial of isoniazid chemoprophylaxis during renal replacement therapy

Abstract: This study shows significant efficacy of INH chemoprophylaxis during RRT in preventing development of TB, when the INH was started during dialysis itself. INH chemoprophylaxis was safe and well tolerated in the majority of patients. However, mild hepatic dysfunction was common, both in the treatment as well as in the control group. As the incidence of viral hepatitis overall was high in our patients on RRT, it is difficult to identify INH-induced hepatitis in this clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 30 publications
4
59
1
Order By: Relevance
“…A patient who had high alanine aminotransferase levels but was negative for anti-HCV and HBsAg was also isolated for haemodialysis unless there was a satisfactory cause for high alanine aminotransferase. This was done as our experience has shown that an unexplained alanine aminotransferase in a haemodialysis setting is mostly due to HBV and HCV viral infection [23]. Patients testing positive for anti-HCV or HBsAg were managed by further testing for HBeAg, HBV-DNA, HCV-RNA and liver biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…A patient who had high alanine aminotransferase levels but was negative for anti-HCV and HBsAg was also isolated for haemodialysis unless there was a satisfactory cause for high alanine aminotransferase. This was done as our experience has shown that an unexplained alanine aminotransferase in a haemodialysis setting is mostly due to HBV and HCV viral infection [23]. Patients testing positive for anti-HCV or HBsAg were managed by further testing for HBeAg, HBV-DNA, HCV-RNA and liver biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…There are data suggesting that INHP is effective in purified protein derivative (PPD) tuberculin skin test-positive patients with haematological malignancies and chronic renal haemodialysis as well as renal transplant recipients [29,30], although the clinical utility of such a strategy has not been fully clarified in clinical practice. The American Thoracic Society recommends the use of INHP in patients receiving glucocorticosteroids at doses equivalent to prednisolone (≥15 mg per day) if they have a positive PPD test [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…(3,33) Use in patients with kidney failure Adjustments to the doses of isoniazid are not required in patients with kidney failure or in those on hemodialysis. (3,4,34) …”
Section: Use In Patients With Liver Failurementioning
confidence: 99%